دور إستراتیجیة المسؤولیة الاجتماعیة للشركات في دعم الأمن الغذائي الشركة السعودیة العربیة للخدمات الزراعیة نموذجا - محمد فلاق; سمیرة أحلام حدو (Finance and Business Economies Review, 2017)
Food security has become a communication strategy in some economics who have integrated it into the general dialogue on corporate social responsibility (CSR). Is food security the responsibility of companies? What are the methods and is there a path to the future for this issue? Since private wealth is rarely redistributed with a view to improving food safety, it will be interesting to observe the practices by several actors in ARASCO company in order to assess the efficiency of the CSR approach. This observation of practice provokes certain reservations. Private initiative must remain a support to State intervention. In all cases, it reveals the need for legal regulation of food security